The effect of naloxone on pulsatile gonadotrophin release in normal subjects. - Moult, P; Grossman, A; Evans, J; Rees, L; Besser, G (1981)
The gonadotrophin response to naloxone infusion has been investigated in three adult males, and three adult females in the early follicular phase. The frequency of LH secretory episodes and the mean LH levels increased in both sexes. The data suggest that the pulsatile release of LH is under inhibitory opiate control.